An investigation of cuticular hydrocarbon variation on Epiachna indica (Coleoptera : Coccinellidae) from Kota Samarahan, Sarawak: Implication for future chemotaxonomic study - Rizoh, Bin Bosorang (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The potential of cuticular hydrocarbon as an alternative method for recognition and classification of Epilachna indica was investigated by examining the distribution and variation of cuticular hydrocarbon across body parts, developmental stages, gender and locality. The relative change in cuticular hydrocarbon was described because changes can occur due to various factors with minimal genetic and karyotypes changes. Cuticular hydrocarbon extracted from 32 samples of Epilachna indica (comprise of 256 individuals) and 18 - 24 individuals each for other species of Coleoptera examined were subjected to gas chromatography/mass spectrometry (GC/MS) analysis of the cuticular hydrocarbons. Seventy out of 120 peaks in gas chromatogram were recognized as cuticular hydrocarbon profile of E. indica) Hydrocarbons were made up over 95% of the cuticular lipids peak areas detected with n-alkanes covered 21.05% of total hydrocarbons extracted, ranging from n-octadecane (n-C18) to n-hexatriacontane (n-C38). The odd-numbered alkanes dominated the distribution of n-alkane in E. indica. Distribution of n-alkanes in E. indica is remaining consistent across body parts, developmental stages and gender with small differences in the proportion of several compounds were observed. Distribution pattern of cuticular hydrocarbons in adult E. indica were wider and more complex compared to pupae and larvae from same species. The distribution pattern of cuticular hydrocarbon between genders also differed with female specimen having more compounds as compared to male specimen. The quantitative differences between genders were clearly distinguished using discriminant function analysis (DFA). There is a variation of 2.50 - 12.36 % between sample within each gender and an average of 32.5 % differences between male and female. DFA was also successfully classified all individuals into their respective group based on locality with cases and cross-validation are 100% and 7.7%, respectively. Cuticular hydrocarbons profile of this beetle was successfully constructed and remarkably different from other species examined in this study. Although the dendogram constructed using n-alkanes data did not compliment with morphological insect classification, however, it has clustered them based on food of the insects. Different genders, localities and species showed different pattern of n-alkanes with sex- and species-specificity, and thus potentially used for sex discrimination and species identification. Information from other types of hydrocarbons such as methyl-branched alkanes and alkenes were also essential for phylogenetic study and may be carried out in future study.